Respuesta :

Answer:

Option B

Step-by-step explanation:

Quadratic equation given in the question is,

[tex]x^2+4x+2=0[/tex]

By comparing this equation with the standard quadratic equation,

[tex]ax^2+bx+x=0[/tex]

[tex]a=1,b=4[/tex] and [tex]c=2[/tex]

By using quadratic formula to get the roots of the given quadratic equation,

[tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]

By substituting the values of a, b and c in the formula,

[tex]x=\frac{-4\pm\sqrt{4^2-4(1)(2)}}{2(1)}[/tex]

[tex]x=\frac{-4\pm\sqrt{16-8}}{2}[/tex]

[tex]x=\frac{-4\pm\sqrt{8}}{2}[/tex]

[tex]x=\frac{-4-\sqrt{8}}{2},\frac{-4+\sqrt{8}}{2}[/tex]

[tex]x=-3.414,-0.5857[/tex]

[tex]x=-3.41,-0.59[/tex]

Therefore, Option B will be the answer.